2019
DOI: 10.1053/j.jrn.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and the Role of Self-Efficacy in a Sodium-Reduction Trial in Hemodialysis Patients

Abstract: Objective: To assess the impact of baseline dietary self-efficacy on the effect of a dietary intervention to reduce sodium intake in hemodialysis (HD) patients, and identify determinants of low dietary self-efficacy.Design: Post-hoc analysis of the BalanceWise study, a randomized controlled trial that aimed to reduce dietary sodium intake in HD patients Setting: 17 dialysis centers in Pennsylvania Subjects: 151 HD patients Main Outcome Measures: Dietary self-efficacy and reported dietary sodium density Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
3
13
0
5
Order By: Relevance
“…43 Furthermore, there are numerous barriers to low-sodium dietary adherence in the United States that have previously been reported. [14][15][16][17] The home-delivered meal approach used in the current study may be a more efficacious approach for reducing sodium intake, especially in patients with higher IDWG's, because it bypasses many of the barriers upon following a low-sodium diet or other renal diet restrictions. However, cost considerations should be taken into account for provision of these meals ($6.99 per renal meal; $587 per patient in this study).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…43 Furthermore, there are numerous barriers to low-sodium dietary adherence in the United States that have previously been reported. [14][15][16][17] The home-delivered meal approach used in the current study may be a more efficacious approach for reducing sodium intake, especially in patients with higher IDWG's, because it bypasses many of the barriers upon following a low-sodium diet or other renal diet restrictions. However, cost considerations should be taken into account for provision of these meals ($6.99 per renal meal; $587 per patient in this study).…”
Section: Discussionmentioning
confidence: 99%
“…13 These findings may be attributed to a high-sodium food environment and a variety of barriers to dietary and behavioral changes. [14][15][16][17] A multitude of other HD dietary restrictions (e.g., phosphorus and potassium) further complicates dietary adherence. 18,19 Recent studies have shown that sodium can be stored in soft tissues, such as skin and muscle, and that elevated tissue sodium is associated with hypertension and left ventricular hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…69 However, in a post hoc analysis of this trial, investigators found that self-efficacy (defined as one's confidence in performing a behavior) was an important determinant of the success of interventions at reducing dietary sodium. 70 Therefore, sodium and fluid restriction interventions that focus on self-efficacy and empowerment may have meaningful impact on outcomes among individuals receiving HD.…”
Section: Dietary Strategiesmentioning
confidence: 99%
“…17 However, an important challenge is to maintain a high protein intake while avoiding concomitant high-salt consumption. In this issue of the Journal of Renal Nutrition, Hu et al 18 assessed the impact of baseline dietary self-efficacy on the effect of a dietary intervention to reduce sodium intake in patients receiving maintenance hemodialysis and found that younger age and perceived income inadequacy were among the determining factors for a low self-efficacy in these patients. These findings 18 may suggest that those with low selfefficacy may benefit the most from interventions that are based on social cognitive therapy to reduce dietary sodium, and hence, more attention should be paid to underlying behavioral constructs such as self-efficacy.…”
Section: Oes Eating Less or More Protein Affect Kidneymentioning
confidence: 99%